2015
DOI: 10.1017/etds.2015.47
|View full text |Cite
|
Sign up to set email alerts
|

Commutator criteria for strong mixing

Abstract: We present new criteria, based on commutator methods, for the strong mixing property of discrete flows $\{U^N\}_{N\in\mathbb Z}$ and continuous flows $\{{\rm e}^{-itH}\}_{t\in\mathbb R}$ induced by unitary operators $U$ and self-adjoint operators $H$ in a Hilbert space $\mathcal H$. Our approach put into evidence a general definition for the topological degree of the curves $N\mapsto U^N$ and $t\mapsto{\rm e}^{-itH}$ in the unitary group of $\mathcal H$. Among other examples, our results apply to skew products… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…So, we infer from the assumption and Cauchy-Schwarz inequality that In the next proposition, we consider the particular case where [iH, A] = f (H) for some Borel function f : R → R. Our results in this case generalise the results of [36,].…”
Section: Lemma 24 (Properties Of D) Let H and A Be Self-adjoint Opera...supporting
confidence: 57%
See 3 more Smart Citations
“…So, we infer from the assumption and Cauchy-Schwarz inequality that In the next proposition, we consider the particular case where [iH, A] = f (H) for some Borel function f : R → R. Our results in this case generalise the results of [36,].…”
Section: Lemma 24 (Properties Of D) Let H and A Be Self-adjoint Opera...supporting
confidence: 57%
“…In recent papers [5,26,29,[33][34][35][36][37][38], it has been shown that one can combine certain tools from dynamical systems (averaging along the dynamics, ergodic theorems) and quantum mechanics (commutator methods) to determine spectral properties of various classes of continuous-and discrete-time models. In particular, a new criterion for strong mixing has been put into evidence in [26,34].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recall in this section some facts borrowed from [7,14] on commutator methods for unitary operators and regularity classes associated with them.…”
Section: Commutator Methods For Unitary Operatorsmentioning
confidence: 99%